2015
DOI: 10.1128/jb.02083-14
|View full text |Cite
|
Sign up to set email alerts
|

Rex (Encoded by DVU_0916) in Desulfovibrio vulgaris Hildenborough Is a Repressor of Sulfate Adenylyl Transferase and Is Regulated by NADH

Abstract: e Although the enzymes for dissimilatory sulfate reduction by microbes have been studied, the mechanisms for transcriptional regulation of the encoding genes remain unknown. In a number of bacteria the transcriptional regulator Rex has been shown to play a key role as a repressor of genes producing proteins involved in energy conversion. In the model sulfate-reducing microbe Desulfovibrio vulgaris Hildenborough, the gene DVU_0916 was observed to resemble other known Rex proteins. Therefore, the DVU_0916 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 48 publications
2
36
1
Order By: Relevance
“…This response is probably linked to the redox status of the cell, as a reducing intracellular environment generated by fermentation is likely to prime cells for sulphate reduction, even if this is not available. Several of these proteins belong to the regulon of the redox-responsive regulator Rex that senses the intracellular NADH/NAD + ratio Ravcheev et al, 2012;Rodionov et al, 2004), is a repressor of the sat gene (Christensen et al, 2015) and is probably involved in this response. A screening of mutants deficient in pyruvate fermentation revealed that deletion of the genes for malic enzyme, fumarate reductase, a dicarboxylate transporter and the NfnAB transhydrogenase led to a strong growth inhibition, whereas mutants in the Rnf and Hdr-Flx proteins had somewhat slower growth than the wild type .…”
Section: Fermentation and Syntrophic Metabolismmentioning
confidence: 97%
See 4 more Smart Citations
“…This response is probably linked to the redox status of the cell, as a reducing intracellular environment generated by fermentation is likely to prime cells for sulphate reduction, even if this is not available. Several of these proteins belong to the regulon of the redox-responsive regulator Rex that senses the intracellular NADH/NAD + ratio Ravcheev et al, 2012;Rodionov et al, 2004), is a repressor of the sat gene (Christensen et al, 2015) and is probably involved in this response. A screening of mutants deficient in pyruvate fermentation revealed that deletion of the genes for malic enzyme, fumarate reductase, a dicarboxylate transporter and the NfnAB transhydrogenase led to a strong growth inhibition, whereas mutants in the Rnf and Hdr-Flx proteins had somewhat slower growth than the wild type .…”
Section: Fermentation and Syntrophic Metabolismmentioning
confidence: 97%
“…More intensive investigations of single transcriptional regulators, such as Fur (Bender et al, 2007), CooA , SahR , Rex (Christensen et al, 2015) and TunR (Kazakov, Rajeev, et al, 2013), have been reported, and a few insights from these studies will be presented below. CooA, the CO sensor (Youn, Kerby, Conrad, & Roberts, 2004) and activator for cooSC, encoding CO dehydrogenase, was shown by the Stahl laboratory to have regulatory functions in D. vulgaris even in the absence of externally added CO .…”
Section: Computational Predictionsmentioning
confidence: 98%
See 3 more Smart Citations